A Narrative Case History of Distance Education Before, During, and After COVID-19 in China and Iran - Keshavarz, Mohsen; Yuan, Li (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
Educational hub refers to centres of excellence in higher education and research whose aims are to provide high-quality education for both national and international students to enhance the competitiveness of the country. These educational hubs provide an opportunity for knowledge exchanges and innovation in local regions through education and training. In response to the COVID-19 pandemic, rapid shifts were made towards online learning in education around the world. Although the lockdown is over, remote learning will likely play an increasingly prominent role in education. The adoption of scaled remote learning during the pandemic provided evidence of the importance of online learning. They offer an insight into global society, helping prepare students for an increasingly interconnected world by facilitating links between different regions. Educational hubs can be tied to distance learning and are successful in attracting international students when offering a combination of distance learning methods and innovative programs. This paper examines the phenomenon of educational hubs in higher education for international education through online learning with digital technology. New opportunities for online and distance learning within the definition of educational hubs are analyzed, and three online and blended learning models that reflect the development of educational hubs based on COVID-19 conditions of education are offered. In addition, the successful cases and experiences of distance learning hubs in China and Iran in recent years are described.